Novel perspectives on swept-source optical coherence tomography. Issue 1 (December 2016) - Lavinsky, Fabio; Lavinsky, Daniel
Abstract Technologies for multimodal digital imaging of vitreoretinal diseases have improved the accuracy of diagnosis and the depth of the knowledge of the mechanisms of disease and their response to treatments. Optic coherence tomography (OCT) has become a mandatory tool for the management and for the follow-up of retinal pathologies. OCT technology evolved in the last two decades from time-domain to spectral domain and recently to the swept-source OCTs (SS-OCT). SS-OCT improved the depth of imaging and the scan speed, thus adding novel algorithms and features such as for vitreous and vitreoretinal interface evaluation, choroid segmentation and mapping, OCT angiography and En-face OCT. The multimodal approach using SS-OCT is expected to advance the understanding of retinal pathologies such as age related macular degeneration, diabetic maculopathy, central serous chorioretinopathy, the pachychoroid spectrum and macular telangiectasia. Surgical vitreoretinal diseases such as vitreo-macular traction syndrome, epiretinal membrane, retinal detachment, proliferative vitreoretinal retinopathy and diabetic traction retinal detachment also will be better understood and documented with SS-OCT. This technology also provides great utility for a broad spectrum of ophthalmic pathologies including glaucoma, uveitis, tumors and anterior segment evaluation.